MODEL DISEMINASI INFORMASI PEMERINTAH KOTA PADANG MELALUI MEDIA SIBER - Gerry Gerry; Elva Ronaning Roem; Rahmi Surya Dewi (Jurusan Ilmu Komunikasi Universitas Andalas, 2018)
The rapid progress of information and communication technology has disrupted the media world. Traditional media is being replaced by cyber media such as websites and social media. This change makes public relations, especially government public relations, to be adaptive and able to make it an opportunity in information dissemination. This study aims to analyze and describe interesting information media models so that people have a tendency to continue to access the development of information through government cyber media. The method used in this study is the method of cyber media analysis. This method emphasizes aspects of media space, media documents, media objects, and experiences. The results of the study show that various forms and models of media display are things that need to be considered to provide a stimulus for someone to access and then read the cyber media used. In addition to the appearance of concern for cyber media users is media content, content is the main thing that should be a concern.